2007
DOI: 10.1126/science.1151710
|View full text |Cite
|
Sign up to set email alerts
|

The Obesity-AssociatedFTOGene Encodes a 2-Oxoglutarate-Dependent Nucleic Acid Demethylase

Abstract: Variants in the FTO (fat mass and obesity associated) gene are associated with increased body mass index in humans. Here, we show by bioinformatics analysis that FTO shares sequence motifs with Fe(II)-and 2-oxoglutarate-dependent oxygenases. We find that recombinant murine Fto catalyzes the Fe(II)-and 2OG-dependent demethylation of 3-methylthymine in single-stranded DNA, with concomitant production of succinate, formaldehyde, and carbon dioxide. Consistent with a potential role in nucleic acid demethylation, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
1,384
4
41

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,376 publications
(1,499 citation statements)
references
References 28 publications
38
1,384
4
41
Order By: Relevance
“…Working together with Tomas Lindahl from the Cancer Research UK labs at South Mimms, UK, and later with Chris Schofield, Chris Ponting, and Fran Ashcroft from Oxford, who had independently spotted the homology, we established unequivocally that FTO was a member of this family of enzymes and was capable of demethylating specific forms of nucleic acid. 48 We also showed that FTO was particularly highly expressed in hypothalamic nuclei concerned with energy balance and, in at least one of those nuclei (the arcuate), that feeding and fasting influence its expression. Although the link between nucleic acid demethylase activity of FTO and its role in obesity is still entirely obscure, the fact that FTO is highly expressed in the hypothalamus and is nutritionally regulated there suggests that it may also play a role in the 'hypothalamic setpoint' of appetite and satiety.…”
Section: Discussionmentioning
confidence: 62%
“…Working together with Tomas Lindahl from the Cancer Research UK labs at South Mimms, UK, and later with Chris Schofield, Chris Ponting, and Fran Ashcroft from Oxford, who had independently spotted the homology, we established unequivocally that FTO was a member of this family of enzymes and was capable of demethylating specific forms of nucleic acid. 48 We also showed that FTO was particularly highly expressed in hypothalamic nuclei concerned with energy balance and, in at least one of those nuclei (the arcuate), that feeding and fasting influence its expression. Although the link between nucleic acid demethylase activity of FTO and its role in obesity is still entirely obscure, the fact that FTO is highly expressed in the hypothalamus and is nutritionally regulated there suggests that it may also play a role in the 'hypothalamic setpoint' of appetite and satiety.…”
Section: Discussionmentioning
confidence: 62%
“…Transgenic larvae with this BAC inserted in their genomes had weak ubiquitous expression that appeared strongest in the eye and in muscle fibers. This is in line with in situ hybridization analyses showing that mouse Fto has low‐level ubiquitous expression (Gerken et al ., 2007; Smemo et al ., 2014). The BAC transgene also confirmed an earlier result with a very similar BAC construct, showing that replacing the first exon of Fto with a lacZ cassette recapitulated the endogenous Fto expression pattern (Smemo et al ., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Modification of brain RNA in wild-type and Fto-knockout mice As shown by Gerken et al, 12 3-methyl-uracil and 3-methyl-thymine in single-stranded RNA and DNA, respectively, are the preferred in vitro substrates of mouse and human Fto/FTO. Given that RNA Total RNA from whole brains of wild-type and Fto À/ À mice was prepared and separated into two fractions: large RNAs (4200 bases) and small (o 200 bases) RNAs.…”
Section: Subcellular Localization Of Ftomentioning
confidence: 95%